Issues and Challenges in Simulation and Modeling (International Journal of Engineering and Computer Science, 2017)
Human mind can process one item at a time and has limitation about capability to relate decision to large amount of background information and can not handle multiple conditions and action situation. Modeling and simulation solve these problems efficiently. It extends understanding of how to build effective and efficient design, evaluation, and operation of new model. The active use of modeling and simulation in various areas are the cause of its popularity in design of engineering and industry. Significant progress has been observed in modeling and simulation over the last few decades, however, many challenging issues remain unresolved, and the current trends tend to use combination of nature-inspired algorithms and surrogate-based techniques for modeling.This paper will analyses the issues and challenges in modeling and simulation in different application areas and discuss important topics for further research and the gaps between theory and applications in different application areas.